2018
DOI: 10.1111/1346-8138.14523
|View full text |Cite
|
Sign up to set email alerts
|

Japanese guidelines for the management and treatment of generalized pustular psoriasis: The new pathogenesis and treatment of GPP

Abstract: Generalized pustular psoriasis (GPP) is a rare disease characterized by recurrent fever and systemic flushing accompanied by extensive sterile pustules. The committee of the guidelines was founded as a collaborative project between the Japanese Dermatological Association and the Study Group for Rare Intractable Skin Diseases under the Ministry of Health, Labour, and Welfare Research Project on Overcoming Intractable Diseases. The aim of the guidelines was to provide current information to aid in the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
479
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(502 citation statements)
references
References 235 publications
(493 reference statements)
10
479
0
13
Order By: Relevance
“…The severity of psoriasis in patients with GPP was also evaluated by the Japanese Dermatological Association (JDA) severity index total score (which ranges from 0 [best] to 17 [worst]), 11 which has been used in clinical trials for GPP. The PASI score and clinical assessment part of the Disease Activity Score with 28 joints (DAS28) using C-reactive protein (CRP) were evaluated by board-certified dermatologists.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of psoriasis in patients with GPP was also evaluated by the Japanese Dermatological Association (JDA) severity index total score (which ranges from 0 [best] to 17 [worst]), 11 which has been used in clinical trials for GPP. The PASI score and clinical assessment part of the Disease Activity Score with 28 joints (DAS28) using C-reactive protein (CRP) were evaluated by board-certified dermatologists.…”
Section: Methodsmentioning
confidence: 99%
“…Psoriatic patients aged 16 years or older who are candidates for systemic therapy and meet any of the following criteria: Patients with plaque‐type psoriasis with or without psoriatic arthritis who meet either of the following criteria: (i) patients who have not adequately responded to any of the standard systemic therapies including phototherapy, with rash covering at least 10% of the body surface area (BSA); and (ii) patients with refractory skin or joint symptoms that are intractable to standard systemic therapies, and significantly impaired QOL. Patients with generalized pustular psoriasis (GPP).Treatment should be performed in accordance with the “Guidelines for diagnosis and treatment of GPP (the 2018 version)” issued by the JDA.No randomized double‐blind clinical studies on biologics have been conducted in patients with GPP because of a limited number of patients. However, reports have shown that patients with GPP responded to TNF inhibitors, IL‐17 inhibitor and IL‐23p19 inhibitors, and infliximab, adalimumab, secukinumab, ixekizumab, brodalumab, guselkumab and risankizumab have been approved with an indication for GPP in Japan.…”
Section: Eligible Patients For Treatment With Biologicsmentioning
confidence: 99%
“…However, reports have shown that patients with GPP responded to TNF inhibitors, IL‐17 inhibitor and IL‐23p19 inhibitors, and infliximab, adalimumab, secukinumab, ixekizumab, brodalumab, guselkumab and risankizumab have been approved with an indication for GPP in Japan. The diagnosis of GPP should follow the criteria stipulated in the “Guidelines for diagnosis and treatment of GPP (the 2018 version)” . Palmoplantar pustulosis, subcorneal pustular dermatosis and acute generalized exanthematous pustulosis are not included in GPP and not indicated for biologic therapy (except guselkumab for palmoplantar pustulosis) Patients with erythrodermic psoriasis.Patient eligibility should be determined after consideration of response to previous treatments, comorbidities, general conditions and other factors.No randomized double‐blind clinical studies on biologics have been conducted in patients with erythrodermic psoriasis because of a limited number of patients.…”
Section: Eligible Patients For Treatment With Biologicsmentioning
confidence: 99%
See 2 more Smart Citations